Diagnostic Performance of a Mnemonic for Warning Symptoms in Predicting Acute Coronary Syndrome Diagnosis: A Retrospective Cross-Sectional Study - Attakowit Sattayaraksa; Thareerat Ananchaisarp; Polathep Vichitkunakorn; Ply Chichareon; Siriwimon Tantarattanapong (Frontiers Media S.A., 2023)
Objectives: We aimed to create a mnemonic for acute coronary syndrome (ACS) warning symptoms and determine its diagnostic performance.Methods: This retrospective cross-sectional study included patients visiting the emergency room with symptoms of suspected ACS during 2020-2021. The mnemonic was created using symptoms with an odds ratio (OR) for predicting ACS >1.0. The mnemonic with the highest OR and sensitivity was identified. Sensitivity analysis was performed to test the diagnostic performance of the mnemonic by patient subgroups commonly exhibiting atypical symptoms.Results: ACS prevalence was 12.2% (415/3,400 patients). The mnemonic, "RUSH ChesT" [if you experience referred pain (R), unexplained sweating (U), shortness of breath (S), or heart fluttering (H) together with chest pain (C), visit the hospital in a timely (T) manner] had the best OR [7.81 (5.93-10.44)] and sensitivity [0.81 (0.77-0.85)]. This mnemonic had equal sensitivity in men and women, the elderly and adults, smokers and non-smokers, and those with and without diabetes or hypertension.Conclusion: The "RUSH ChesT" mnemonic shows good diagnostic performance for patient suspected ACS. It may effectively help people memorize ACS warning symptoms.